2011
DOI: 10.1007/978-3-642-20769-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Data Protection, Privacy and Identity: Distinguishing Concepts and Articulating Rights

Abstract: Abstract. The purpose of this article is to provide a sound and coherent articulation of the rights to data protection, privacy and identity within the EU legal framework. For this purpose, the paper provides a number of important criteria through which the three different rights in question can be clearly defined, distinguished and articulated. Although intrinsically interrelated, the article draws attention to the importance of keeping the rights and concepts of data protection, privacy and identity explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Having said that, we find it interesting that at the light of existing EU regulation the Puddick's court case were not treated as a privacy matter for two reasons. First, if someone's identity is falsified or an erroneous public image of his/her personality is conveyed to others, we have a case for identity infringement (Andrade, 2011) -Mr. Puddick had created a false identity in LinkedIn to connect to Mr. Hayne's acquaintances and further defame him. Andrade and other authors argue that privacy is infringed "if true private facts related to a person are revealed to the public".…”
Section: Discussion: Privacy Concerns In the Two Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Having said that, we find it interesting that at the light of existing EU regulation the Puddick's court case were not treated as a privacy matter for two reasons. First, if someone's identity is falsified or an erroneous public image of his/her personality is conveyed to others, we have a case for identity infringement (Andrade, 2011) -Mr. Puddick had created a false identity in LinkedIn to connect to Mr. Hayne's acquaintances and further defame him. Andrade and other authors argue that privacy is infringed "if true private facts related to a person are revealed to the public".…”
Section: Discussion: Privacy Concerns In the Two Casesmentioning
confidence: 99%
“…A myriad of authors (e.g. De Hert and Gutwirth, 2006;Poullet, 2010;Andrade, 2011) have devoted a great deal of attention to study current provisions of European Union (EU) law on privacy matters. We found through two recent cases of social media usage that many privacy functions and properties are neither contemplated in the law nor even articulated in the normative discourses that permeate society, namely those echoed by news media.…”
mentioning
confidence: 99%
“…Personal data is any information relating to an individual who can be identified, either directly or indirectly, from that data (or from that data in combination with other data) (GDPR Art. 4 (1)). Personal data may include not only names, addresses, ID numbers, and so on, but also potentially device IDs, IP addresses (dynamic or static), online identifiers, and a range of other data relating to the specific characteristics of the individual.…”
Section: Gdpr: Rights and Obligationsmentioning
confidence: 99%
“…In relation to subject access and portability requests, they must provide information without undue delay and in a concise, transparent, intelligible and easily accessible form (Art. 12 (1)). This can be done in writing or electronically.…”
Section: B Obligations Imposed: Rights and Securitymentioning
confidence: 99%
“…9. For a more detailed explanation of the difference and articulation between the rights to data protection, privacy and identity, see Andrade, 2011. 10.…”
Section: Data Protection -Privacy -Identitymentioning
confidence: 99%